Interplay of geometrical and spin chiralities in 3D twisted magnetic ribbons - André M. A. Farinha; See-Hun Yang; Jiho Yoon; Banabir Pal; Stuart S. P. Parkin (Nature, 2025)
Abstract Chirality is a ubiquitous and fundamental asymmetry in nature1,2. Recently, the interaction of chiral objects with spin currents has attracted enormous attention from both scientific and technological perspectives3–5. Of particular interest is the current-driven motion of chiral topological excitations such as chiral magnetic domain walls in chiral three-dimensional magnetic structures that could allow for high-density memory-storage devices. Here we use state-of-the-art multiphoton lithography6,7 to create three-dimensional chiral magnetic ribbons and perform current-induced motion of chiral domain walls. The ribbons are designed to have a clockwise or anticlockwise chiral twist with a variable magnitude. We find that domain walls can either pass through the ribbon or are impeded, depending on their chirality and configuration and the geometrical chiral twist of the ribbon. The interplay between the magnetic exchange energy and the geometrical twist generates a torsional field that favours chiral Bloch-type walls rather than the Néel-type wall favoured by the intrinsic magnetic properties of the magnetic ribbon itself. Furthermore, the interplay of spin chirality and chiral twist results in a non-reciprocal domain wall motion, namely, a domain wall filter or diode8–10. Our findings show how the interplay between geometrical and spin chiralities can lead to new functionalities that could allow for innovative chiral spintronics.